PENGARUH KUALITAS SISTEM PENDAFTARAN ONLINE PADA APLIKASI MOBILE JKN TERHADAP KEPUASAN PASIEN RAWAT JALAN DI RSU PERMATA HUSADA BANTUL DAERAH ISTIMEWA YOGYAKARTA - Fakhruddin Fauzan; Susatyo Herlambang (JMMU: JURNAL MAHASISWA MANAJEMEN DAN UMUM, 2026)
This study aims to determine the Effect of the Quality of the Online Registration System on the Mobile JKN Application on Outpatient Satisfaction at Permata Husada Bantul DIY Hospital. This study uses a quantitative approach with a survey method. The population in this study were patients who used the online registration service on the Mobile JKN application, with a sample of 50 respondents using a purposive sampling technique. Data were collected through observation, questionnaires, documentation and literature studies by obtaining research results that there is a positive and significant effect of the quality of the online registration system on the Mobile JKN application on user satisfaction, with this significance <0.05 (0.000 <0.005) and a determination coefficient value of 0.536 indicating that 53.6% on the level of user satisfaction. With this, improving the quality of the system for online registration on the Mobile JKN application can increase the satisfaction of outpatients at Permata Husada Bantul DIY Hospital.